The business rules : - Eichenbaum, David A. (Entrepreneur Press, 2007)
They apply without exception to any organization in the world. Following them has led Coke to prosper over Pepsi, Microsoft over Apple, Southwest over larger carriers and Toyota over General Motors. David Eichenbaum has devoted 20 years of extensive research to identifying these seven primary drivers. They account for all business successes and failures. You probably know at least three of them, maybe more. They are timeless and enduring, simple to implement and definitive . . . yet very few companies master them all. The companies that master these rules have the blueprint to prosperity.